Essays in the History of Ideas - Lovejoy, Arthur O. (Johns Hopkins University Press, 2019)
Originally published in 1948. In the first essay of this collection, Lovejoy reflects on the nature, methods, and difficulties of the historiography of ideas. He maps out recurring phenomena in the history of ideas, which the essays illustrate. One phenomenon is the presence and influence of the same presuppositions or other operative "ideas" in very diverse provinces of thought and in different periods. Another is the role of semantic transitions and confusions, of shifts and of ambiguities in the meanings of terms, in the history of thought and taste. A third phenomenon is the internal tensions or waverings in the mind of almost every individual writer-sometimes discernible even in a single writing or on a single page-arising from conflicting ideas or incongruous propensities of feeling or taste to which the writer is susceptible. These essays do not contribute to metaphysical and epistemological questions; they are primarily historical.